Implementing Collaborative and Concrete Learning to Improve First Graders’ Understanding of Children’s Rights and Responsibilities through Thematic Activities - Rahayu, Dwi Vivi; Rosidah, Cholifah Tur (WAHANA, 2026)
This study aims to improve first-grade elementary students’ understanding of rights and responsibilities through the implementation of collaborative and concrete learning models in Civic Education (PPKn). The method used was Classroom Action Research (CAR) conducted in two cycles, consisting of the stages of planning, implementation, observation, and reflection. Data were collected through observations, tests, interviews, and documentation, and were analyzed using descriptive qualitative and quantitative methods. The results showed a significant improvement in students’ ability to distinguish between rights and responsibilities, as well as increased participation and discipline both at school and at home. The collaborative and concrete learning models proved effective in creating an enjoyable and meaningful learning environment